A case of miriplatin-induced lung injury. Issue 7 (July 2016) - Kumasawa, Fumio; Miura, Takao; Takahashi, Toshimi; Endo, Daisuke; Ohki, Takashi; Nakagawara, Hiroshi; Maruoka, Shuichiro; Tsujino, Ichiro; Masahiro, Ogawa; Gon, Yasuhiro; Takahashi, Noriaki; Moriyama, Mitsuhiko; et al.
Abstract: A 69-year-old man with an 8-year history of hepatocellular carcinoma (HCC) was hospitalized for treatment of recurrent tumour. In 2010, the first transcatheter arterial chemoembolization (TACE) using miriplatin with agents (Lipiodol Ultra-Fluid) was performed and did not occur any adverse events. In 2014, since his HCC recurred, the TACE using miriplatin with agents was performed. Following this therapy, pyrexia occurred on day 3, followed by respiratory failure with cough and dyspnea on day 5. Chest radiography revealed scattered infiltration in the right upper lung fields, and chest computed tomography revealed ground grass attenuations, indicating fibrotic non-specific interstitial pneumonia. These findings progressively deteriorated, and a diagnosis of miriplatin-induced lung injury was made. His respiratory failure also progressively deteriorated. Treatment with pulse methylprednisolone therapy resulted in a dramatic improvement in both patient symptoms and radiological abnormalities.